The efficacy and safety of low-intensity focused ultrasound pulses for prolonged disorders of consciousness: a study protocol for a randomized controlled trial - Di, Haibo; Huang, Yuehong; Yu, Qiuyi; Liu, Hongxiang; Xue, Chenxia; Schnakers, Caroline; Laureys, Steven; Monti, Martin M. (Frontiers in Neurology, 2025)
BackgroundRecent randomized controlled trials (RCTs) in patients with prolonged disorders of consciousness (pDoC) have yielded limited success. Among them, only studies involving amantadine have provided Class II evidence. The effects of other non-invasive brain stimulation techniques remain inconclusive, largely due to patient heterogeneity and the clinical complexities of implementing such interventions. Low-intensity focused ultrasound pulses (LIFUP), as a novel, non-invasive, and safe neuromodulation technique, have the potential to both stimulate and inhibit deep subcortical structures. This makes LIFUP a promising approach for modulating consciousness and promoting recovery in patients with pDoC. This study aims to evaluate the therapeutic efficacy and safety of LIFUP through a randomized controlled design.Methods and analysisOur primary research focus involves conducting multimodal neurofunctional assessments throughout the intervention period. Specifically, we intend to investigate the relationship between Blood Oxygen Level-Dependent (BOLD) signals, electroencephalography (EEG) patterns, thalamic concentrations of glutamate and glutamine (Glx) and gamma-aminobutyric acid (GABA) and behavioral outcomes under two different LIFUP parameter settings (100 Hz transcranial ultrasound stimulation [TUS] and theta-burst TUS [tbTUS]).DiscussionThrough a comprehensive exploration of parameter setting combined with multimodal neurofunctional assessments, this study evaluates both therapeutic potential and safety considerations of ultrasound-based interventions for pDoC. We hypothesize that the two stimulation protocols (100 Hz TUS and tb TUS) will differentially modulate neural connectivity, thalamus activity, and the Glx/GABA balance. The findings may advance evidence-based interventions for pDoC and identify potential neuroplasticity biomarkers to guide future therapeutic strategies.Clinical trial registrationChinese Clinical Trial Registry, ChiCTR2400092904. Registered on 26 November 2024.